Embracing Change in the Context of Paternal Postpartum Depression: A Concept Analysis Using the Walker and Avant Method - Shintya, Lea Andy (NUTRIX, 2026)
The transition to fatherhood requires significant emotional and behavioral adaptation, yet many fathers experience depression when unable to adjust to their new roles. Understanding "embracing change" as a concept is essential for developing effective nursing interventions to support paternal mental health and family well-being. Purpose, this concept analysis aims to clarify the meaning, defining characteristics, antecedents, and consequences of "embracing change" in the context of paternal postpartum depression and maternity nursing care. Method, The Walker and Avant systematic concept analysis method was employed to examine the concept through comprehensive literature review and case construction. Key Findings, "Embracing change" in the paternal context is characterized by three essential attributes: (1) strong self-awareness of emotions and changing identity, (2) a supportive environment providing empathy and validation, and (3) effective communication with partners and healthcare providers. Antecedents include resilience, adaptability, and prior coping experiences. Positive consequences include improved mental health, enhanced family relationships, and increased paternal involvement in child-rearing. This concept analysis provides nursing with a comprehensive framework for understanding how fathers adapt to parenthood and manage postpartum depression. Future research should develop interventions to support fathers in embracing change and examine long-term mental health outcomes. Transisi menjadi seorang ayah memerlukan adaptasi emosional dan perilaku yang signifikan, namun banyak ayah mengalami depresi ketika tidak dapat menyesuaikan diri dengan peran baru mereka.  Memahami “menerima perubahan” sebagai sebuah konsep sangat penting untuk mengembangkan intervensi keperawatan yang efektif guna mendukung kesehatan mental ayah dan kesejahteraan keluarga.  Analisis konsep ini bertujuan untuk memperjelas makna, karakteristik yang mendefinisikan, anteceden, dan konsekuensi dari “menerima perubahan” dalam konteks depresi postpartum paternal dan perawatan keperawatan maternitas. Metode analisis konsep sistematis Walker dan Avant digunakan untuk meneliti konsep tersebut melalui tinjauan pustaka yang komprehensif dan konstruksi kasus.  Temuan Utama, “Menerima perubahan” dalam konteks paternal ditandai oleh tiga atribut penting: (1) kesadaran diri yang kuat terhadap emosi dan perubahan identitas, (2) lingkungan yang mendukung dengan empati dan validasi, dan (3) komunikasi yang efektif dengan pasangan dan penyedia layanan kesehatan.  Anteceden mencakup ketahanan, adaptabilitas, dan pengalaman mengatasi sebelumnya.  Konsekuensi positif termasuk kesehatan mental yang lebih baik, hubungan keluarga yang lebih baik, dan peningkatan keterlibatan ayah dalam pengasuhan anak. Analisis konsep ini memberikan perawat kerangka kerja yang komprehensif untuk memahami bagaimana para ayah beradaptasi dengan peran sebagai orang tua dan mengelola depresi pascapersalinan.  Penelitian selanjutnya harus mengembangkan intervensi untuk mendukung para ayah dalam menerima perubahan dan meneliti hasil kesehatan mental jangka panjang.